Thought work thinking, action, and the fate of the world - Minnich, Elizabeth Kamarck; Patton, Michael Quinn 1945- (Rowman & Littlefield, 2019)
Thought, though an essential part of our lives, is very under appreciated. This under appreciation of careful thought and thinking is damaging to our society. The editors gather together thought leaders to share their views on how to respond to this dilemma